Novel active packaging based on films of chitosan and chitosan/quinoa protein printed with chitosan-tripolyphosphate-thymol nanoparticles via thermal ink-jet printing. (January 2016) - Caro, Nelson; Medina, Estefanía; Díaz-Dosque, Mario; López, Luis; Abugoch, Lilian; Tapia, Cristian
Abstract: New active packaging films based on chitosan (Qo) and a blend of Qo and quinoa-protein (EPQ) were developed. The films were printed with chitosan-tripolyphosphate nanoparticles (NQos) and NQos loaded with thymol (NQoThs) using inkjet printing. Films were prepared by casting high-viscosity Qo and Qo/EPQ solutions (different ratios). Films suitable for printing were selected based on their mechanical properties and low levels of water uptake under simulated fresh-fruit storage conditions. The ionic gelation of low molecular weight Qo with tripolyphosphate produced 60-nm spherical nanoparticles, as seen with TEM. Before the NQoTh suspension was printed into films, 20% glycerol was added to modify the surface tension and kinematic viscosity of the suspension. Adding glycerol increased the Z-average and PDI by 24% and 12%, respectively, and decreased the Z-potential by 15%. Both NQoTh printed films had enhanced barrier properties compared with the control. The efficiency of thymol (Th) incorporation by inkjet printing was dependent on the number of printed layers, the contact angle, the amount of glycerol added to the dispersion, and the film type. Th release assays using Franz cells indicated continuous delivery from both films for 8 days. The differences in the Th-release profiles of the films were attributed to differences in NQoTh locations on the films. The NQoTh-printed films exhibited higher antimicrobial activity against Listeria innocua, Staphylococcus aureus, Salmonella typhimurium, Enterobacter aerogenes, Pseudomonas aeruginosa, and Escherichia coli than NQo-printed and control films. The utilisation of nanotech-printables can improve the functionality of films created from renewable biopolymers. This technology will also enable the development of new packaging materials to extend the shelf life of fresh fruits. Graphical abstract: Highlights: Qo 1.5% and blend Qo/EPQ films were suitable for printing process. NQoTh-suspension was printed successfully on the films. NQoTh-Printed films exhibited improved water vapour barrier properties. Thymol-release profiles were locations dependent of NQoTh after its printing. NQoTh-Films printed showed higher AM against Gram-positive and Gram-negative bacteria.